HUBUNGAN DUKUNGAN SUAMI DENGAN KECENDRUNGAN DEPRESI PADA IBU POSTPARTUM DI PUSKESMAS - Pertiwi, Thayakinta (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
In postpartum period the mother will experience physical changes and psychological changes. If mother is not able to adapt to the conditions, then her will experience serious psychological disorder is postpartum depression. There is support right for husband was able to help the mother in preventing postpartum depression. This study aims to determine the relationship of husband support the tendency of postpartum depression in mother. This type of research is correlational with cross-sectional approach. The sample consisted of 41 mothers postpartum were selected using consecutive sampling. Collecting data using the Edinburgh Postnatal Depression Scale questionnaire (EPDS) and  questionnaire of husband support. The results showed most mothers get a good husband support and are less likely to experience postpartum depression was 56.1%, there were 7 (17.1%) mothers were postpertum get support and are less likely to experience depression and contained 12.2% of postpartum mothers get support and less likely to experience postpartum depression. The results of Chi-Square statistical test with a significance level of p < 0.05 was obtained outcomes p = 0.000, then H0 is rejected, it means that there is a significant relationship between husband support with postpartum depression tendency. Based on the results of this study suggested that health practitioners screening test as well as increased knowledge of the importance of the support of the husband to prevent the tendency of postpartum depression in the mother.
Keywords: Tendency Of Postpartum Depression; Husband Support